The impact of audit committee effectiveness on the relationship between company performance and readability of disclosures: a laboratory experiment - Munandar, Agus; Kadlina, Kadlina (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This paper investigated the impact of audit committees on the relationship between company performance and disclosure readiness.Design/Methodology/Approach: Some research suggested that poorly performing companies often present their performance positively but use complex, less accessible language. This can be detrimental to market participants. The study explored the moderating role of audit committees in this relationship using a laboratory experiment. Participants, including employed students, were placed in scenarios with varying company performance and audit committee effectiveness and tasked with simulating financial disclosures.Research findings: The findings revealed that effective audit committees enhance disclosure readability and significantly moderate the relationship between company performance and disclosure readability. High-performing companies tend to use simpler language, while poorly performing companies often employ complex language to obscure their performance.Theoretical contribution/Originality: This research contributes to the literature by highlighting the role of audit committee effectiveness in ensuring transparent and clear financial disclosures. It extends previous findings by emphasizing different disclosure strategies based on performance and the critical role of audit committees in curbing obfuscation by underperforming firms.Practitioner/Policy implication: The results underscored the importance of audit committee effectiveness in improving corporate governance and maintaining investor trust. Policymakers should promote audit committee independence and expertise to ensure higher standards of disclosureResearch limitation/Implication: The study's use of employed students limits generalizability to professional accountants. Nonetheless, it provides valuable insights into the influence of audit committees on disclosure readability, offering a basis for future research.